Kumkapı, Istanbul: Immigrant Waves and ‘For Rent’ Signs in the Linguistic Landscape - Wendel, John ("Intercultural Dialogues" Transactions, 2023)
This paper presents new data from a third survey of ‘For Rent’ signs in the Kumkapı district of Istanbul conducted in June 2023. Kumkapı is gathering place and home for many of Istanbul’s transit and new-arrival immigrants, refugees, and asylum seekers, making this district a unique vantage point from which to document change in a dynamic language ecology. First, I review the earlier two linguistic landscape surveys of ‘For Rent’ signs; the first survey was completed in January 2017, the second 18 months later in July 2018. There were significant differences found across the two surveys, e.g., in the latter, representing a major shift in language regimes, there was a far greater proportion of Uzbek to Turkish signs compared to the first January 2017 survey. Meanwhile, between the second July 2018 survey and this third June 2023 survey period, there has been a consequential five-year interval: in addition to elections, immigration and refugee issues have intensified across Turkey, and the world has experienced a global pandemic, lockdowns, and geopolitical upheavals. The data from the June 2023 is evaluated in the context of the earlier surveys and events of the five-year interval. The questions this paper addresses are, (1) What changes in the Kumkapı signage are observed across survey periods? and, (2) How can the changes be interpreted and explained? What emerges from the new data is familiar, but at the same time, it brings to light surprising adaptations to the changes in Kumkapı’s rental market.